Factors related to abdominal pain in gastroparesis: contrast to patients with predominant nausea and vomiting. Issue 5 (17th February 2013) - Hasler, W. L.; Wilson, L. A.; Parkman, H. P.; Koch, K. L.; Abell, T. L.; Nguyen, L.; Pasricha, P. J.; Snape, W. J.; McCallum, R. W.; Sarosiek, I.; Farrugia, G.; Calles, J.; et al.
Abstract Background Factors associated with abdominal pain in gastroparesis are incompletely evaluated and comparisons of pain vs other symptoms are limited. This study related pain to clinical factors in gastroparesis and contrasted pain/discomfort‐ with nausea/vomiting‐predominant disease. Methods Clinical and scintigraphy data were compared in 393 patients from seven centers of the NIDDK Gastroparesis Clinical Research Consortium with moderate‐severe (Patient Assessment of Upper Gastrointestinal Disorders Symptoms [PAGI‐SYM] score ≥3) vs none‐mild (PAGI‐SYM < 3) upper abdominal pain and predominant pain/discomfort vs nausea/vomiting. Key Results Upper abdominal pain was moderate‐severe in 261 (66%). Pain/discomfort was predominant in 81 (21%); nausea/vomiting was predominant in 172 (44%). Moderate‐severe pain was more prevalent with idiopathic gastroparesis and with lack of infectious prodrome (P ≤ 0.05) and correlated with scores for nausea/vomiting, bloating, lower abdominal pain/discomfort, bowel disturbances, and opiate and antiemetic use (P < 0.05), but not gastric emptying or diabetic neuropathy or control. Gastroparesis severity, quality of life, and depression and anxiety were worse with moderate‐severe pain (P ≤ 0.008). Factors associated with moderate‐severe pain were similar in diabetic and idiopathic gastroparesis. Compared to predominant nausea/vomiting, predominant pain/discomfort was associated with impaired quality of life, greater opiate, and less antiemetic use (P < 0.01), but similar severity and gastric retention. Conclusions & Inferences Moderate‐severe abdominal pain is prevalent in gastroparesis, impairs quality of life, and is associated with idiopathic etiology, lack of infectious prodrome, and opiate use. Pain is predominant in one fifth of gastroparetics. Predominant pain has at least as great an impact on disease severity and quality of life as predominant nausea/vomiting.